К теории словосочетания (на материале курдского языка) - Хамоян, Максим («Զանգակ - 97»)
In this paper we prove, that subordinate word combinations formed from requirement in marking types of displaying objects of reality, marking them as the crucial components.
Keywords: Лингвистика; Курдский язык